Optimal site for applying transcutaneous bilirubinometer as an outpatient screening tool for neonatal jaundice: a comparison between the sternum and forehead - Zhang, Emily; Wu, Tzong-Jin; Hudak, Mark L.; Yan, Ke; Teng, Ru-Jeng (Frontiers in Pediatrics, 2024)
The standard neonatal jaundice (NJ) test is serum total serum bilirubin (TSB). Transcutaneous bilirubinometer (TCB) provides a convenient, noninvasive readout within minutes. The reliability of TCB and the proper site for TCB measurement remains unsettled. This study aimed to evaluate the reliability of TCB in outpatient NJ management and identify a better place for TCB readings. This retrospective study examines data collected over 15 months at a level-III facility. Parents were advised to bring their neonates back if neonates were judged to be at risk for NJ. Those who had received phototherapy or sustained forehead bruising were excluded. The primary endpoint was admission for treatment according to the AAP 2004 guidelines. A mixed-effects model was used to assess the correlation of forehead TCB (TCB-f) or sternal TCB (TCB-s) with TSB by adjusting for gestational age (GA), sex, and race. Repeated Measure Receiver Operator Characteristic curves were constructed for TCB against admission, and the cutoffs for each method were selected to study the sensitivity. There were 500 visits for 350 neonates. GA was 38.5±1.6 weeks, and birthweight (BW) was 3238±506 grams. Forty-five neonates (12.9%) were admitted, but only 43 had enough data for comparison. After adjusting for age of measurement, GA, sex, and race, both TCB-f and TCB-s positively correlated with TSB (p<0.0001). Using repeated measure ROC, with admission as the primary outcome, the area under the curve (AUC) for TCB-f was 0.79 (95% CI: 0.71-0.86), and AUC for TCB-s was 0.86 (95% CI: 0.81-0.92). A cutoff of 14.3 for TCB-s gave a sensitivity of 81% and a specificity of 78%. A cutoff of 12.6 for TCB-f gave a sensitivity of 80% and a specificity of 65%. TCB can predict admission for NJ in our nursery but tends to underestimate the severity. The sternum is a better site for TCB measurements. We must point out that more than 40% of neonates who should be admitted for NJ management would be sent home if TSB-s were not obtained. We recommend adjusting TCB readings according to unit-based calibration before clinical implementation.